(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
BACKGROUND: Skin diseases are a major public health concern in India with an estimated 6.3 – 11.6 % of population affected. [1] Due to the varied nature of clinical presentations of skin lesions ranging from inflammatory non-neoplastic lesions to neoplasms, histopathological assessment of skin biopsy is essential to provide accurate diagnosis and guide patient management. [1][2] This study evaluated the spectrum of skin lesions diagnosed through punch biopsy at a tertiary care center in Bhavnagar, Gujarat. MATERIALS AND METHODS: Retrospective analysis was conducted on 113 consecutive skin punch biopsy samples received at the Department of Pathology, Government Medical College, Bhavnagar during September 2024 to August 2025. All samples were fixed in 10 % formalin; processed routinely; cut into 4-5µm sections; and stained using H&E. Special stains (i.e., Fite-Faraco, PAS) were performed as necessary to support diagnosis. Clinical information (patient age, gender, lesion type, location) was collected. Descriptive statistics were applied to describe the findings. RESULTS: Among 113 patients, 62 (54.9 %) were females while 51 (45.1 %) were males (Female:Male ratio = approximately 1.2 : 1). Patient’s ages ranged from 6 to 75 years with a mean age of 44.8 years. The most common age groups were 31-40 years (n=26, 23.0%), followed by 51-60 years (n=21, 18.58%). Hypopigmented patches were the most common clinical presentation (n=31, 27.4%), followed by hyperpigmented patches (n=14, 12.4%). The most common biopsy site was the back (n=26, 23.0%). Hansen’s disease (leprosy) was the largest histopathologic category and comprised 49 (43.4 %) of all biopsy samples. The Borderline Lepromatous subtype was the most common among these (n=17/49, 34.7%). Papulosquamous disorders were the second-most common category (n=17, 15.0%) and consisted primarily of lichen planus (n=10, 58.8% of papulosquamous category) and psoriasis (n=5, 29.4%). Nonspecific dermatitis represented 9 (8.0%) biopsy samples and included allergic contact dermatitis as the most common (n=5/9, 55.6%). A total of 8 patients (7.1%) were diagnosed with vesiculobullous diseases, with pemphigus vulgaris representing the majority (n=5, 62.5% of the vesiculobullous group). (Tables 1–3, Figures 1–3). These findings are similar to other studies published in India. For example, Dawande et al. [3] (Nagpur), similarly found that leprosy (24%) and pemphigus (10%) were common. CONCLUSION: Evaluation of skin biopsy samples demonstrated a broad range of dermatopathologies. Leprosy was again the most common diagnosis identified in the present Gujarat cohort. The findings highlight the importance of performing skin biopsy to correctly classify dermatological lesions in order to apply effective treatment, particularly in areas endemic for infectious and inflammatory skin diseases.[1][3]